3(X+15)-4(11-X)=5X

Simple and best practice solution for 3(X+15)-4(11-X)=5X equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(X+15)-4(11-X)=5X equation:


Simplifying
3(X + 15) + -4(11 + -1X) = 5X

Reorder the terms:
3(15 + X) + -4(11 + -1X) = 5X
(15 * 3 + X * 3) + -4(11 + -1X) = 5X
(45 + 3X) + -4(11 + -1X) = 5X
45 + 3X + (11 * -4 + -1X * -4) = 5X
45 + 3X + (-44 + 4X) = 5X

Reorder the terms:
45 + -44 + 3X + 4X = 5X

Combine like terms: 45 + -44 = 1
1 + 3X + 4X = 5X

Combine like terms: 3X + 4X = 7X
1 + 7X = 5X

Solving
1 + 7X = 5X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-5X' to each side of the equation.
1 + 7X + -5X = 5X + -5X

Combine like terms: 7X + -5X = 2X
1 + 2X = 5X + -5X

Combine like terms: 5X + -5X = 0
1 + 2X = 0

Add '-1' to each side of the equation.
1 + -1 + 2X = 0 + -1

Combine like terms: 1 + -1 = 0
0 + 2X = 0 + -1
2X = 0 + -1

Combine like terms: 0 + -1 = -1
2X = -1

Divide each side by '2'.
X = -0.5

Simplifying
X = -0.5

See similar equations:

| n^2+15n+50= | | -4(3x-2)-(-x+6)=-5x+8 | | 168-2x=43+23 | | x/5-3=0 | | 10m+5(m-4)=-80 | | 9-(5+3x)+5x=-4(x-3)-7 | | 15=2x+5 | | (6x+32)(x-12)=(5x+30)(x-13) | | (7/8)s=91 | | 14-7x=62-35x | | 5X-(3X+4)=12 | | 8-(4-2n)-4= | | 1/(x-2)-2x=(x-1)/(x-2) | | 9-(2n-9)=3-3n | | 5/6+6=9 | | 7-10x=122-45x | | 5x+11=129-9x | | 2=3x-16 | | 8(8+w)=7(4+w) | | 5a+3(a+2)=30 | | 1/x-2+2x=x-1/x-2 | | 2z+1=3z | | -2(3y-4)=3-y | | 4(10y-6)=-5 | | 7x+3=4x+66 | | x=2,1/35/9 | | 8/2+5(7-3) | | 9/4+(3/4x+2)^2=0 | | 10x-2=25x+1 | | 3a+6b=18 | | 3t-2= | | -2x+2-4=-2(-x+4) |

Equations solver categories